CSIG-16. SEXUAL DIMPORHISM IN IRON ACQUISITION IN GLIOBLASTOMA. (9th November 2020) - Pandya, Bhavyata; Slagle-Webb, Becky; Nesterova, Darya; Zacharia, Brad; Lathia, Justin; Rubin, Joshua; Berens, Michael; Barnholtz-Sloan, Jill S; Connor, James
Abstract: Glioblastoma (GBM) is the most aggressive brain cancer. Sex differences in incidence and clinical outcomes have been reported, however, our knowledge of contributing mechanisms is limited. Iron acquisition is key to robust tumor growth. Upregulation of Transferrin (Tf, iron transport protein)/Transferrin receptor (TfR) is found in multiple different cancers. We have identified H-ferritin (FTH1) as involved in iron transport and explore its uptake in GBM in this study. We interrogated iron uptake in a syngeneic orthotopic mouse model (GL261 cells) using male and female mice. After the tumors were established, radioactive 125 I labeled Tf and FTH1 proteins were injected retro-orbitally in the mice. After 24 hours, tumors were removed, homogenized and analyzed for Tf and FTH1 uptake. There was a significant difference in Tf uptake into the tumor versus matched non-tumor tissue in both males and females and the uptake in the tumors was 1.5-fold higher in males than females. There was no significant difference in FTH1 uptake between male and female tumors nor between tumor and matched non-tumor brain tissue. Binding analyses were performed on homogenized samples of human male and female GBM tissue samples using 125 I labeled Tf and FTH1. Tumors from males had increased binding of both proteins compared to tumors from females. We next queried the TCGA database and found in females, high TfR expression was associated with poor survival but not in males. TCGA database revealed a robust expression of Tim1, a putative receptor for FTH1, but its expression did not relate to survival. In summary, this study demonstrates FTH1 binding to GBMs and sexual dimorphism in iron acquisition via Tf and survival.